Prediction of the Phase Composition Profile of Three‐Compound Mixtures in Liquid‐Liquid Equilibrium: A Chemoinformatics Approach. Issue 24 (5th September 2022) - Carrera, Gonçalo V. S. M.; Cruz, Mariana L.; Klimenko, Kyrylo; Esperança, José M. S. S.; Aires‐de‐Sousa, João
Abstract: Machine‐learning models were developed to predict the composition profile of a three‐compound mixture in liquid‐liquid equilibrium (LLE), given the global composition at certain temperature and pressure. A chemoinformatics approach was explored, based on the MOLMAP technology to encode molecules and mixtures. The chemical systems involved an ionic liquid (IL) and two organic molecules. Two complementary models have been optimized for the IL‐rich and IL‐poor phases. The two global optimized models are highly accurate, and were validated with independent test sets, where combinations of molecule1+molecule2+IL are different from those in the training set. These results highlight the MOLMAP encoding scheme, based on atomic properties to train models that learn relationships between features of complex multi‐component chemical systems and their profile of phase compositions. Abstract : The MOLMAP encoding method, based on the atomic pattern of activation of a given chemical system on a Kohonen neural network, was used to represent: a‐ a three‐compound mixture (ionic liquid+molecule1+molecule2) and b‐ molecule1 or molecule2 of that mixture at certain temperature and pressure. The Random Forest algorithm predicts its phase behaviour profile.